FUNCTIONALIZATION MAGNETITE ACTIVATED CARBON COATINNG WITH SILANE AGENT AS ADSORBENT FOR CRYSTAL VIOLET AND METHYL ORANGE DYES - Annisaa Siti Zulaicha; Candra Saka Nusantari; Arif Setiajaya (Jurusan Kimia FMIPA Universitas Lampung, 2024)
Indonesia, the largest palm oil producer, produces a very large of palm kernel shell waste. This study aims to optimize utilization of this waste by converting it into activated carbon which has high potential adsorbent. Process making activated carbon involves carbonization and activation of palm kernel shells, followed by surface modification using magnetic particles and organosilane triethoxyiphenylsilane (TEPS). Addition of Fe3O4 particles can increase adsorption capacity and facilitate the separation of the adsorbent from the solution after adsorption process. Meanwhile, addition of TEPS compounds increases the number of functional groups on the surface of activated carbon so can interact more strongly with dye molecules. Characterization using various techniques such as UV-Vis, FTIR, XRD, SEM-EDX, and BET was carried out to analyze changes structure and surface properties of activated carbon after modification. The results of the study can contribute to development of waste processing technology and production of value-added adsorbent materials.